Children with Cerebral Palsy and Unmet Need for Care Coordination. Issue 8 (October 2021) - Casseus, Myriam; Cheng, JenFu
ABSTRACT: Objective: To examine the physical and functional health of children with cerebral palsy (CP) and determine the prevalence and correlates of unmet need for health care coordination among this population. Methods: We analyzed data from the 2016 to 2018 National Survey of Children's Health (n = 102, 341). Bivariate and multivariable analyses were conducted to compare the prevalence of chronic health conditions, functional disabilities, and care coordination among children with and without CP. Multivariable logistic regression models were used to estimate the adjusted odds ratio of comorbid conditions, functional disabilities, and unmet need for care coordination. Associations between select sociodemographic factors and unmet need for care coordination were assessed. Results: Children with CP had significantly higher prevalence of all the comorbid conditions and functional disabilities examined. The most prevalent health conditions among children with CP were allergies (34.2%), anxiety (26.5%), and asthma (25.1%). Notably, children with CP had higher odds of autism spectrum disorder (adjusted odds ratio [aOR] = 2.97; 95% confidence interval [CI] 1.40–6.30) and mental health conditions (aOR = 3.65; 95% CI 2.15–6.21). More than half (53.8%) of children with CP had unmet need for care coordination. They also had higher odds of unmet need for care coordination than children without CP (aOR = 2.63; 95% CI 1.69–4.10). Conclusion: Children with CP have high prevalence of chronic health conditions and are also more likely to have unmet need for care coordination. Given the complexity of CP, our study supports the need for robust efforts to ensure that all children with CP have effective care coordination.